2019
DOI: 10.32664/j-intech.v6i02.253
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Game Virtual Reality Berbasis Android Menggunakan Unity Sebagai Media Penunjang Pengenalan Bahasa Inggris

Abstract: Perkembangan teknologi membuat dunia memanfaatkan teknologi pada dunia edukasi, saat ini terdapat beberapa perubahan trend pada digital education, salah satu trend tersebut adalah edukasi yang memanfaatkan teknologi Augmented Reality dan Virtual Reality. Virtual reality merupakan teknologi yang mengijinkan seorang pengguna untuk berinteraksi dengan sebuah lingkungan yang disimulasikan oleh komputer. Teknologi tersebut mengijinkan pengguna untuk berinteraksi di dalam dunia virtual. Salah satu edukasi atau pendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Among them the research conducted by (Dharma et al, 2018) on early childhood (PAUD) who found that there was an effect of using virtual reality media on student learning outcomes. Other researchers have revealed that the use of virtual reality provides several benefits in authentic learning in 21st century language classes (Utami et al, 2021); (Andre, Handriyantini, & Oktavia, 2019) in their research conclusion stated that virtual reality technology can be implemented into an educational game on the android platform by using Unity 3D as the game engine.…”
Section: Introductionmentioning
confidence: 99%
“…Among them the research conducted by (Dharma et al, 2018) on early childhood (PAUD) who found that there was an effect of using virtual reality media on student learning outcomes. Other researchers have revealed that the use of virtual reality provides several benefits in authentic learning in 21st century language classes (Utami et al, 2021); (Andre, Handriyantini, & Oktavia, 2019) in their research conclusion stated that virtual reality technology can be implemented into an educational game on the android platform by using Unity 3D as the game engine.…”
Section: Introductionmentioning
confidence: 99%
“…Bahasa internasional yang digunakan sebagai sarana untuk berkomunikasi adalah Bahasa Inggris (Farizah & Astiningrum, 2016); (Al Irsyadi, Annas, & Kurniawan, 2019); (Andre, Handriyantini, & Oktavia, 2018). Bahasa inggris merupakan bahasa yang telah diakui sebagai bahasa pemersatu bahasa (Marlianingsih, 2016).…”
Section: Pendahuluanunclassified
“…According to Lestari (2018), technology in education is a system that is usually used to support learning so that the desired results can be achieved. One of the educational technologies that are currently trending is virtual reality (VR) (Andre et al, 2019;Endarto & Martadi, 2022;Rasim et al, 2022). VR has been developing since the 1800s; however, VR is a new technology used in education (Erbas & Demirer, 2019).…”
Section: Introductionmentioning
confidence: 99%